Analysis of the Effectiveness of Accounting Information Systems in the Local Government of Medan City - Muhammad Ipan; Yunita Sari Rioni; Vina Arnita (Universitas Dehasen Bengkulu, 2026)
The development of information technology has encouraged local governments to implement Accounting Information Systems (AIS) to improve transparency, accountability, and efficiency in regional financial management. However, the implementation of AIS in the Medan City Government still faces several challenges, including limited human resource competence, inadequate technological infrastructure, and lack of system integration. This study aims to analyze the effectiveness of the Accounting Information System in the Medan City Government using the DeLone and McLean Information Systems Success Model. This research employs a quantitative approach, with data collected through questionnaires distributed to 80 local government financial management officers. Data analysis techniques include validity testing, reliability testing, normality testing, and heteroscedasticity testing, processed using SPSS software. The results indicate that all research instruments are valid and reliable, and the data meet the classical assumptions of regression analysis. System quality, information quality, and service quality have a positive effect on system use and user satisfaction. Furthermore, system use and user satisfaction positively influence the effectiveness of the Accounting Information System. Overall, the Accounting Information System implemented by the Medan City Government is categorized as effective; however, improvements in service quality and continuous development of human resource competencies are still required to optimize the implementation of the system.